Aplikasi Belajar Menulis Untuk Anak Prasekolah Berbasis Android - Hendrawan, Heny Sidarta; Sunarto, M. J. Dewiyani; Sutanto, Teguh (Jurnal JSIKA, 2012)
The ability to write the beginning of a major provision for children to be able to understand the subjects given at school. One of alternatives for helping increases the interest and the ability of the children in learning to read and write is using the media of learning in the form of software. Android is a software alternative were chosen, with the reason android tend to be used on mobile devices such as Smartphone and tablet PC, in addition to ease of android in development was offered due to easy it is to get the source and tutorials as well as being one of the reasons the android was chosen as the medium to build this application. The results of this research thesis is an application that presents study writing with packaged like play the game. While in the stage of testing applications through quantitative and qualitative testing have shown a positive response from the respondent to use this application as an alternative media  learn to write.   Keyword : Learn to write, Preschool age children, Android